Piezoelectric energy harvesting for low power electronic devices - Lim, Wilson Benedict Ye Xiang. (2012)
Piezoelectric is sometimes seen far more reliable compared to solar energy harvesting as it does not depend on the weather conditions. This FYP is dealing with piezoelectric energy generation which can be used for powering low energy devices such as remote controllers, clocks, mp3 etc. The aim of this project is to design an efficient harvesting circuit to store the charges and use it for powering those devices. The amount of energy lost when the charges are being stored in a rechargeable battery/super capacitor must be minimal. The prototype would be done up such that the piezoelectric material can generate as much charges as possible in a given area upon compression with a force.